Additives in foods marketed to children in Uruguay, an emerging Latin American country - Florencia Alcaire; Ana Giménez; Gastón Ares (Journal of Nutritional Science)
Foods are frequently marketed to children through the inclusion of a wide range of elements on the packages. Several studies conducted in different countries around the globe have shown that products marketed to children are usually high in sugar and other nutrients associated with non-communicable diseases. The present exploratory cross-sectional study aimed at providing additional evidence on the composition of products marketed to children by analysing the disclosure of additives in such products. Data were collected at nine supermarkets in two Uruguayan cities between August and October 2021. All packaged products available in each supermarket were surveyed using a cell phone app, except for culinary ingredients. All the information from the labels was extracted. Products marketed to children were identified based on the presence of indicators of child-directed marketing on the package. The disclosure of additives was analysed based on the information available in the ingredient list. The prevalence of food additive disclosure was calculated. Of the 7,343 products included in the database, 573 (7.8%) were classified as marketed to children. Candies and cookies were the categories with the largest number of products marketed to children. The great majority of the products marketed to children disclosed at least one food additive (93.5%). These products tended to more frequently notify colourings, antioxidants, acidity regulators, raising agents, stabilisers, humectants, anticaking agents, and glazing agents compared to products not marketed to children. These findings underscore the need to expand the current scope of regulations on marketing targeted at children beyond nutrients to include additives potentially linked to adverse health effects, such as artificial colourings.